2021
DOI: 10.1108/bij-06-2021-0363
|View full text |Cite
|
Sign up to set email alerts
|

Development of a sustainable brand identity model: fostering the implementation of SDGs in the Brazilian power sector

Abstract: PurposeThis study aims to develop a sustainable brand identity model to help organizations align their managerial practices to sustainable development goals (SDGs) and examine its applicability for a Brazilian electrical sector company.Design/methodology/approachA systematic qualitative review of the literature was carried out to provide a theoretical basis for the attributes chosen to compose the sustainable brand identity management (SBIM) model. To apply the model, the authors collected the data from intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…The method in this study is divided into theoretical development (model development) and empirical part (model application). Several authors have used this method to propose brand management models for other contexts (Caldana et al , 2021; Florek et al , 2021; Kanazawa et al , 2021; Lourenção and Giraldi, 2017; Urde and Greyser, 2016). Figure 1 presents the methodological flowchart showing an overview of the research process at the empirical and theoretical levels.…”
Section: Methodsmentioning
confidence: 99%
“…The method in this study is divided into theoretical development (model development) and empirical part (model application). Several authors have used this method to propose brand management models for other contexts (Caldana et al , 2021; Florek et al , 2021; Kanazawa et al , 2021; Lourenção and Giraldi, 2017; Urde and Greyser, 2016). Figure 1 presents the methodological flowchart showing an overview of the research process at the empirical and theoretical levels.…”
Section: Methodsmentioning
confidence: 99%
“…With regards to the articles' impact, the paper with the highest number of citations in relative terms was that by van der Waal et al (2021) [165], whereas the paper with more total citations was that by Ike et al (2019) [166]. Conversely, there were two papers with no citations: Caldana et al (2021) [167], and Galleli et al (2021) [17].…”
Section: Research Subtopicsmentioning
confidence: 98%
“…They can raise awareness and use symbolism to strongly sway customers' opinions about a brand. Caldana et al (2021) state that identity is a management construct that defines the proper characteristics to describe an organization's organizational operations internally. Liu et al (2020) found that brand identity is a company's unique idea and the way it conveys this notion to its numerous stakeholders.…”
Section: Identitymentioning
confidence: 99%